A semi-rigid anti-freezing and anti-fatigue gypsum pavement base material and a preparation method thereof

CN122916580APending Publication Date: 2026-10-16WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511198627.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-26
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本申请提供了一种半刚性抗冻抗疲劳磷石膏路面基层材料及其制备方法,解决或部分解决了只能将磷石膏作为添加料或辅助材料在道路工程中进行应用,掺量太低无法实现废弃磷石膏规模化资源化利用,且磷石膏在道路材料运用时存在疲劳性能较差,在极端环境下存在开裂的技术问题,实现磷石膏固废高效资源转化,所制备材料不仅满足道路工程力学性能指标要求,且具备优异的抗疲劳及抗冻性能

Benefits of technology

[0025] This application uses waste phosphogypsum as the main raw material, with phosphogypsum accounting for 60% to 80% of the road surface materials. This achieves high-volume and efficient utilization of waste phosphogypsum in road base materials, effectively mitigating industrial solid waste and reducing stockpiling pollution. Calcium carbide slag replaces part of the cement, reducing carbon emissions and neutralizing the acidity of the phosphogypsum, thus reducing secondary treatment costs. Cement and calcium carbide slag provide initial alkalinity, accelerating the formation of ettringite and CSH gels. Simultaneously, highly active SiO2 and Al2O3 from silica fume and metakaolin continuously participate in the pozzolanic reaction, filling pores. Free phosphorus and fluorine in the phosphogypsum are solidified; the Ca2+ in the calcium carbide slag... + It forms CaF2 precipitate with F-, and the alkaline environment promotes the conversion of phosphorus into stable phosphate, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to a semi-rigid anti-freezing and anti-fatigue phosphogypsum pavement base material, which comprises the following components: phosphogypsum, cement, carbide slag, silica fume, metakaolin and a composite emulsion, the mass fraction of the composite emulsion in the solidified component is (1-5)%; the solidified component comprises: phosphogypsum 60-80%, cement 5-10%, carbide slag 5-15%, silica fume 5-15% and metakaolin 5-15%; the mass ratio of emulsified asphalt emulsion to polymer emulsion in the composite emulsion is (7-9):(1-3); the phosphogypsum pavement base material can effectively promote the resource utilization of phosphogypsum solid waste, and can promote the utilization of carbide slag, silica fume and other solid wastes; the pavement base material prepared by the method has excellent road performance, fatigue performance and anti-freezing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and in particular to a semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material and its preparation method. Background Technology

[0002] Phosphogypsum is an industrial byproduct of the wet process for producing phosphoric acid in phosphate fertilizer plants. For every ton of phosphoric acid produced, 4.5 to 5.5 tons of phosphogypsum are generated as a byproduct, with global stockpiles exceeding 6 billion tons and China's annual increase being approximately 80 million tons. Open-air stockpiling of phosphogypsum presents three major problems: it contains soluble phosphorus, fluorine, and heavy metals, easily seeping into the soil and groundwater with rainwater, causing environmental pollution; the need for continuous expansion of phosphogypsum stockpiles encroaches on arable land and ecological space, occupying a large amount of land; and wet-discharge of phosphogypsum stockpiles poses a risk of dam failure and other safety hazards. Therefore, accelerating the comprehensive utilization of phosphogypsum has become an urgent task.

[0003] Currently, research on the application of phosphogypsum in road engineering mainly focuses on its use as a low-dosage additive or auxiliary material, while research and practice on its use as a major component to replace natural aggregates in road base courses are relatively scarce. Natural crushed stone, as a key aggregate in road base courses, is a non-renewable mineral resource. The rapid development of road construction in China has led to the massive consumption of natural sand and gravel, and its mining process inevitably exacerbates the contradiction between ecological damage and resource depletion. Therefore, utilizing phosphogypsum on a large scale to replace natural aggregates in road base courses is of great significance for achieving resource conservation and environmental protection.

[0004] However, the inherent strong hydrophilicity of phosphogypsum makes it easy to soften when it comes into contact with water. When used as a base material, it faces key bottlenecks such as difficulty in strength formation and poor water stability, which seriously restricts its engineering application. Summary of the Invention

[0005] This application provides a semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material and its preparation method, which solves or partially solves the technical problems that phosphogypsum can only be used as an additive or auxiliary material in road engineering, the dosage is too low to achieve large-scale resource utilization of waste phosphogypsum, and phosphogypsum has poor fatigue performance and cracking under extreme environments when used in road materials. It realizes the efficient resource conversion of phosphogypsum solid waste. The prepared material not only meets the mechanical performance requirements of road engineering, but also has excellent fatigue resistance and antifreeze properties.

[0006] The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material provided in this application includes the following components: phosphogypsum, cement, carbide slag, silica fume, metakaolin and composite emulsion. The phosphogypsum, cement, carbide slag, silica fume and metakaolin constitute the consolidation component, and the composite emulsion accounts for (1-5)% of the mass fraction of the consolidation component.

[0007] The consolidation components, by mass percentage, comprise: 60-80% phosphogypsum, 5-10% cement, 5-15% carbide slag, 5-15% silica fume, and 5-15% metakaolin.

[0008] The composite emulsion includes an emulsified asphalt emulsion and a polymer emulsion, wherein the mass ratio of the emulsified asphalt emulsion to the polymer emulsion is (7-9):(1-3).

[0009] Preferably, the emulsified asphalt is a cationic emulsified asphalt with a solid content of 30-50% and a pH value of 2.0-5.0.

[0010] Preferably, the polymeric emulsion includes, but is not limited to: styrene-butadiene latex, silicone-acrylic emulsion, epoxy resin emulsion, EVA emulsion, and vinyl acetate-acrylic emulsion.

[0011] Preferably, the phosphogypsum is obtained by drying, cooling and pulverizing waste phosphogypsum produced in industry;

[0012] The particle size distribution of the phosphogypsum is below 0.3 mm.

[0013] Preferably, the cement can be replaced with a mixture of cement and mineral admixtures;

[0014] The cement may be PO42.5 grade ordinary Portland cement, PO32.5 grade ordinary Portland cement, or sulfoaluminate cement.

[0015] Preferably, the carbide slag has a specific gravity of 2.7–2.9 g and a particle diameter of 0.088–0.25 mm.

[0016] Preferably, the silica fume has a density of 2.20–2.50 g / cm³, an average particle size of 0.1–0.3 μm, and a specific surface area of ​​22–26 m². 2 / g.

[0017] Preferably, the metakaolin has a density of 2.50-2.60 g / cm³ and a specific surface area of ​​15-20 m². 2 / g.

[0018] Based on the same inventive concept, this application also provides a method for preparing a semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material, comprising the following steps:

[0019] Waste phosphogypsum is dried, cooled, crushed, and sieved to obtain the phosphogypsum.

[0020] The phosphogypsum is mixed evenly with the cement, the carbide slag, the silica fume, and the metakaolin to obtain mixture A;

[0021] After mixing the composite emulsion with water and stirring until homogeneous, mixture B is obtained;

[0022] After mixing the mixture A and the mixture B evenly, the semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is obtained.

[0023] Preferably, the temperature in the drying process of the waste phosphogypsum is controlled at 70℃~120℃ and the time is controlled at 12h~16h.

[0024] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages:

[0025] This application uses waste phosphogypsum as the main raw material, with phosphogypsum accounting for 60% to 80% of the road surface materials. This achieves high-volume and efficient utilization of waste phosphogypsum in road base materials, effectively mitigating industrial solid waste and reducing stockpiling pollution. Calcium carbide slag replaces part of the cement, reducing carbon emissions and neutralizing the acidity of the phosphogypsum, thus reducing secondary treatment costs. Cement and calcium carbide slag provide initial alkalinity, accelerating the formation of ettringite and CSH gels. Simultaneously, highly active SiO2 and Al2O3 from silica fume and metakaolin continuously participate in the pozzolanic reaction, filling pores. Free phosphorus and fluorine in the phosphogypsum are solidified; the Ca2+ in the calcium carbide slag... + It forms CaF2 precipitate with F-, and the alkaline environment promotes the conversion of phosphorus into stable phosphate, reducing environmental pollution.

[0026] Meanwhile, the composite emulsion introduced in this application, in which emulsified asphalt particles are dispersed in water, forms a hydrophobic film after demulsification. The demulsified emulsified asphalt then covers the aggregate surface, forming a flexible interfacial transition layer. The chemical bonding between the polymer film and the inorganic phase enhances interfacial adhesion and reduces interfacial debonding under cyclic loading. Simultaneously, the polymer emulsion solidifies to form a flexible polymer network, creating a stable system that fills pores and encapsulates inorganic hydration products. When microcracks propagate, the polymer chains absorb energy through tensile deformation, inhibiting crack penetration. Asphaltenes in the emulsified asphalt migrate to the capillary walls, forming a hydrophobic film that reduces pore surface energy and hinders water adsorption and intrusion. The solidified polymer emulsion seals interconnected pores, reducing the content of freezeable water. The resulting polymer has an elastic modulus far lower than that of cement stone, absorbing expansion stress through deformation during frost heave, preventing the rigid structure from collapsing. Simultaneously, the composite emulsion lowers the freezing point of water and slows down the ice crystal growth rate. Detailed Implementation

[0027] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following examples are commercially available. The cement used was P.O42.5 grade ordinary Portland cement produced by a certain company; phosphogypsum was a light gray acidic powder, prone to caking, and weakly acidic. In the following comparative examples and examples, the mechanical properties of phosphogypsum pavement base materials were tested according to the test methods of "Highway Geotechnical Test Procedures" (JTGE 400-2007) and "Highway Engineering Inorganic Binder Stabilized Materials Test Procedures" (JTG 3441-2024).

[0029] Comparative Example 1

[0030] A road base material, its composition and test results are as follows:

[0031] According to the corresponding mixing ratio, all the required raw materials are weighed quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 60%, cement 8%, carbide slag 12%, silica fume 10%, metakaolin 10%; water accounts for 20% of the total mass of the consolidation component. The preparation process is as follows: mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin evenly and let stand to obtain mixture A; pour water and mixture A into a mixing pot and stir continuously for 140 seconds to obtain the road base material; then prepare samples and cure according to the test procedure.

[0032] Performance testing: Standard specimens with a diameter of 50mm and a diameter of 50mm were made by static pressing according to the test procedure, with a compaction degree of >98%. They were then placed in a standard curing chamber (20℃±2, humidity ≥95%) and cured to the required age. On the last day of the curing period, the specimens were taken out and soaked in water at 20℃±2 for 24 hours. After removing them and wiping the surface moisture with a soft cloth, an unconfined compressive strength test was conducted at a loading rate of 1mm / min. Six parallel specimens were used, and their representative values ​​were taken.

[0033] Following the fatigue test method (Method B) for inorganic binder stabilized materials in the test procedure, plate specimens of 430mm × 300mm × 80mm were prepared. The plate specimens were then cut using a high-precision diamond double-sided saw. Beam specimens were fabricated with the rolling forming direction as the specimen length direction. The specimen dimensions should meet the requirements of length 380mm ± 0.5mm, thickness 51mm ± 0.5mm, and width 63.5mm ± 0.5mm. The specimens were placed in a standard curing chamber (20℃ ± 2, humidity ≥ 95%) and cured until the required age. On the last day of the curing period, the specimens were removed and immersed in water at 20℃ ± 2 for 24 hours. After removing them and wiping the surface dry with a soft cloth, fatigue tests were conducted on the inorganic binder stabilized materials using strain control mode. Six parallel specimens were used, and representative values ​​were taken.

[0034] The specimens were statically pressed according to the test procedure to form standard specimens with a diameter of Φ150mm×h150mm and a compaction degree of >98%. They were then placed in a standard curing chamber (20℃±2, humidity ≥95%) and cured until the required age for inorganic binder freeze-thaw test. Six parallel specimens were used, and their representative values ​​were taken.

[0035] Tests showed that the fatigue lives of the standard specimens obtained in Comparative Example 1 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 104,587, 50,832, 14,367, and 2,007 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 6.37, 6.12, 6.03, 5.48, 5.20, and 4.32, respectively; and the BDR after five freeze-thaw cycles was 67.8%.

[0036] Comparative Example 2

[0037] A road base material, its composition and test results are as follows:

[0038] According to the corresponding mixing ratio, weigh all the required raw materials in quantitative quantities. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 60%, cement 8%, carbide slag 7%, silica fume 12.5%, metakaolin 12.5%; water accounts for 20% of the total mass of the consolidation component.

[0039] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Comparative Example 2 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 95,421, 46,326, 13,103, and 1,831 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 9.25, 9.20, 8.73, 8.03, 7.77, and 6.75, respectively; and the BDR after five freeze-thaw cycles was 73.0%.

[0040] Comparative Example 3

[0041] A road base material, its composition and test results are as follows:

[0042] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 8%, carbide slag 12%, silica fume 5%, metakaolin 5%; water accounts for 20% of the total mass of the consolidation component.

[0043] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Comparative Example 3 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 92,318, 44,815, 12,673, and 1,771 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 14.24, 12.98, 11.33, 10.76, 10.43, and 9.71, respectively; and the BDR after five freeze-thaw cycles was 68.2%.

[0044] Comparative Example 4

[0045] A road base material, its composition and test results are as follows:

[0046] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70%, cement 8%, carbide slag 7%, silica fume 7.5%, metakaolin 7.5%; water accounts for 20% of the total mass of the consolidation component.

[0047] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Comparative Example 4 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 84,762, 41,149, 11,637, and 1,626 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 10.73, 9.55, 8.93, 8.62, 7.34, and 6.68, respectively; and the BDR after five freeze-thaw cycles was 62.3%.

[0048] Comparative Example 5

[0049] A road base material, its composition and test results are as follows:

[0050] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 8%, carbide slag 12%, silica fume 0%, metakaolin 0%; water accounts for 20% of the total mass of the consolidation component.

[0051] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Comparative Example 5 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 66,582, 32,324, 9,141, and 1,277 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 11.07, 10.72, 10.23, 9.73, 8.36, and 7.57, respectively; and the BDR after five freeze-thaw cycles was 68.4%.

[0052] Comparative Example 6

[0053] A road base material, its composition and test results are as follows:

[0054] According to the corresponding mixing ratio, weigh all the required raw materials quantitatively. The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80%, cement 8%, carbide slag 7%, silica fume 2.5%, metakaolin 2.5%; water accounts for 20% of the total mass of the consolidation component.

[0055] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Comparative Example 6 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 55,473, 26,932, 7,617, and 1,064 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 11.54, 10.42, 10.02, 9.43, 8.65, and 8.01, respectively; and the BDR after five freeze-thaw cycles was 69.4%.

[0056] Example 1

[0057] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner similar to that of Comparative Example 1, except that a composite emulsion is added.

[0058] The raw materials and their mass percentages in the consolidation components are as follows: phosphogypsum 60.0%, cement 8.0%, carbide slag 12.0%, silica fume 10.0%, and metakaolin 10.0%.

[0059] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0060] After testing (using the same testing method as Comparative Example 1), the fatigue lives of the standard specimens obtained in Example 1 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 118,642, 57,606, 16,291, and 2,276 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 7.57, 7.48, 7.25, 7.01, 6.78, and 6.55, respectively; and the BDR after five freeze-thaw cycles was 86.5%.

[0061] Example 2

[0062] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0063] The raw materials in the consolidation component and their mass percentages are as follows: phosphogypsum 60.0%, cement 8.0%, carbide slag 12.0%, silica fume 10.0%, metakaolin 10.0%; water accounts for 20% of the total mass of the consolidation component.

[0064] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0065] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 2 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 144,361, 70,123, 19,342, and 2,698 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 8.21, 8.12, 7.98, 7.83, 7.67, and 7.32, respectively; and the BDR after five freeze-thaw cycles was 89.2%.

[0066] Example 3

[0067] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0068] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 60.0%, cement 8.0%, carbide slag 7.0%, silica fume 12.5%, metakaolin 12.5%; water accounts for 20% of the total mass of the consolidation component.

[0069] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0070] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 3 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 113,872, 55,286, 15,635, and 2,185 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 11.33, 11.20, 11.02, 10.78, 10.45, and 10.15, respectively; and the BDR after five freeze-thaw cycles was 89.6%.

[0071] Example 4

[0072] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0073] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 60.0%, cement 8.0%, carbide slag 7.0%, silica fume 12.5%, metakaolin 12.5%; water accounts for 20% of the total mass of the consolidation component.

[0074] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0075] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 4 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 138,659, 67,319, 18,582, and 2,591 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 13.29, 13.15, 12.95, 12.70, 12.38, and 11.05, respectively; and the BDR after five freeze-thaw cycles was 83.1%.

[0076] Example 5

[0077] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0078] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70.0%, cement 8.0%, carbide slag 12.0%, silica fume 5.0%, metakaolin 5.0%; water accounts for 20% of the total mass of the consolidation component.

[0079] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0080] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 5 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 107,283, 52,089, 14,731, and 2,058 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 17.34, 17.15, 16.75, 16.38, 15.92, and 15.26, respectively; and the BDR after five freeze-thaw cycles was 88.0%.

[0081] Example 6

[0082] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0083] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70.0%, cement 8.0%, carbide slag 12.0%, silica fume 5.0%, metakaolin 5.0%; water accounts for 20% of the total mass of the consolidation component.

[0084] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0085] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 6 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 130,742, 63,477, 17,551, and 2,452 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 20.63, 20.42, 19.98, 19.52, 18.86, and 17.75, respectively; and the BDR after five freeze-thaw cycles was 86.0%.

[0086] Example 7

[0087] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0088] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70.0%, cement 8.0%, carbide slag 7.0%, silica fume 7.5%, metakaolin 7.5%; water accounts for 20% of the total mass of the consolidation component.

[0089] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0090] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 7 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 98,456, 47,803, 13,519, and 1,889 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 14.82, 14.65, 14.32, 13.92, 13.48, and 12.37, respectively; and the BDR after five freeze-thaw cycles was 83.5%.

[0091] Example 8

[0092] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0093] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 70.0%, cement 8.0%, carbide slag 7.0%, silica fume 7.5%, metakaolin 7.5%; water accounts for 20% of the total mass of the consolidation component.

[0094] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0095] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 8 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 120,037, 58,276, 16,482, and 2,303 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 15.33, 15.17, 14.92, 14.60, 14.20, and 13.65, respectively; and the BDR after five freeze-thaw cycles was 89.0%.

[0096] Example 9

[0097] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0098] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80.0%, cement 8.0%, carbide slag 12.0%, silica fume 0.0%, metakaolin 0.0%; water accounts for 20% of the total mass of the consolidation component.

[0099] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0100] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 9 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 76,318, 37,055, 10,480, and 1,464 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 15.41, 15.25, 14.98, 14.65, 14.25, and 13.70, respectively; and the BDR after five freeze-thaw cycles was 88.9%.

[0101] Example 10

[0102] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0103] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80.0%, cement 8.0%, carbide slag 12.0%, silica fume 0.0%, metakaolin 0.0%; water accounts for 20% of the total mass of the consolidation component.

[0104] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0105] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 10 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 93,025, 45,165, 12,773, and 1,784 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 16.72, 16.55, 16.23, 15.85, 15.38, and 14.81, respectively; and the BDR after five freeze-thaw cycles was 88.6%.

[0106] Example 11

[0107] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0108] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80.0%, cement 8.0%, carbide slag 7.0%, silica fume 2.5%, metakaolin 2.5%; water accounts for 20% of the total mass of the consolidation component.

[0109] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 1%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0110] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 11 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 63,572, 30,865, 8,729, and 1,219 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 14.20, 14.05, 13.78, 13.45, 12.77, and 11.25, respectively; and the BDR after five freeze-thaw cycles was 79.2%.

[0111] Example 12

[0112] A semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is prepared in a manner largely similar to that in Example 1.

[0113] The raw materials and their mass percentages in the consolidation component are as follows: phosphogypsum 80.0%, cement 8.0%, carbide slag 7.0%, silica fume 2.5%, metakaolin 2.5%; water accounts for 20% of the total mass of the consolidation component.

[0114] Mix phosphogypsum, cement, carbide slag, silica fume, and metakaolin until homogeneous and let stand to obtain mixture A; mix composite emulsion (composed of emulsified asphalt and styrene-butadiene emulsion in a mass ratio of 8:1) with water until homogeneous and let stand to obtain mixture B, with the mass percentage of composite emulsion and consolidation component being 3%; pour mixture A and mixture B into a mixing pot and stir continuously for 140 seconds to obtain phosphogypsum pavement base material; then prepare samples and cure according to the test procedure.

[0115] After testing (using the same testing method as in Example 1), the fatigue lives of the standard specimens obtained in Example 12 under stress ratios of 0.70, 0.75, 0.80, and 0.85 were 77,483, 37,617, 10,638, and 1,486 cycles, respectively; the strength of the standard specimens after each freeze-thaw cycle was 16.30, 16.13, 15.82, 15.43, 14.98, and 13.04, respectively; and the BDR after five freeze-thaw cycles was 80.0%.

[0116] Table 1 Mix proportions of different phosphogypsum pavement base materials

[0117]

[0118]

[0119] Table 2. Fatigue test results (stress control) of different phosphogypsum pavement base materials

[0120]

[0121]

[0122]

[0123]

[0124] Based on the fatigue test results of the base materials with different proportions in Table 2, it can be found that the examples with added composite emulsion exhibit significantly stronger fatigue life than the comparative examples under various stress ratios. Under a stress ratio of 0.70, the fatigue life of the examples containing emulsion is generally improved by more than 15%, with Example 2 showing a 38.0% improvement over Comparative Example 1 and Example 4 showing a 45.3% improvement over Comparative Example 2. In the critical stress range of 0.75, the life improvement of the emulsion group reaches 22%-45%. Among them, under a high stress ratio of 0.85, the composite emulsion can still effectively delay failure, such as Example 2 showing a 34.4% improvement in life compared to Comparative Example 1 and Example 4 showing a 41.5% improvement in life compared to Comparative Example 2, proving that the composite emulsion can significantly enhance the material's resistance to dynamic loads. Furthermore, the proportion of phosphogypsum has a particularly significant impact on fatigue performance: the 80% high-phosphogypsum group has a life of only 26,932-32,324 cycles under a stress ratio of 0.75, while the addition of emulsion increases it to 37,055-45,165 cycles, with an improvement rate of 37%-67.7%, indicating that the composite emulsion can effectively compensate for the mechanical defects of high-phosphogypsum.

[0125] Table 3 shows the intensity of the 28-day curing freeze-thaw cycle test for the comparative and example cases.

[0126]

[0127]

[0128] Based on the 28-day freeze-thaw cycle strength data of different base material ratios in Table 3, it can be found that the composite emulsion improves freeze-thaw durability to a certain extent. All examples containing emulsion showed a strength retention rate (BDR) > 79.2% after 5 freeze-thaw cycles, which was stronger than the 62.3%-73.0% of the control group without emulsion. Example 3 had the highest BDR, reaching 89.6%. The contrast in freeze-thaw strength decay was striking: Control Group 1 experienced a strength loss of 32.3%, while Example 2 containing emulsion only lost 10.8%. The proportion of phosphogypsum was negatively correlated with freeze-thaw performance: Examples 9-12 with 80% high phosphogypsum had higher initial strengths of 15.41-16.72 MPa, but their BDR was slightly lower than the 60%-70% phosphogypsum group. Examples 11-12 had the lowest BDR among the emulsion group, at only 79.2%-80.0%. After 5 freeze-thaw cycles, the examples containing the composite emulsion exhibited better durability. The strength retention rate (BDR) of these composite emulsions is generally higher than 70%, which is stronger than that of the comparative group. In particular, in the same phosphogypsum formulation, the strength difference after freeze-thaw cycles can be several times. The hydrophobic barrier formed by the composite emulsion effectively inhibits water penetration and freeze-thaw damage, fundamentally improving the material's resistance to freeze-thaw degradation.

[0129] Composite emulsions alter material properties through a triple synergistic effect: by filling pores and bridging particles with polymers, they can improve density and load transfer efficiency; by blocking water erosion, they form a hydrophobic film to prevent water penetration and inhibit ice crystal damage during freeze-thaw cycles; and by buffering stress and relaxing dry and wet shrinkage stress through flexible chains, they can reduce crack initiation and propagation. Their core value lies in simultaneously overcoming the strength bottleneck and environmental tolerance shortcomings of phosphogypsum-based materials, providing key technical support for road engineering applications.

[0130] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A semi-rigid, freeze-thaw resistant, and fatigue-resistant phosphogypsum pavement base material, characterized in that, It includes the following components: phosphogypsum, cement, carbide slag, silica fume, metakaolin and composite emulsion, wherein the phosphogypsum, cement, carbide slag, silica fume and metakaolin constitute a consolidation component, and the composite emulsion accounts for (1-5)% of the mass fraction of the consolidation component. The consolidation components, by mass percentage, comprise: 60-80% phosphogypsum, 5-10% cement, 5-15% carbide slag, 5-15% silica fume, and 5-15% metakaolin. The composite emulsion includes an emulsified asphalt emulsion and a polymer emulsion, wherein the mass ratio of the emulsified asphalt emulsion to the polymer emulsion is (7-9):(1-3).

2. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The emulsified asphalt is a cationic emulsified asphalt with a solid content of 30-50% and a pH value of 2.0-5.

0.

3. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The polymer emulsions include, but are not limited to: styrene-butadiene latex, silicone-acrylic emulsion, epoxy resin emulsion, EVA emulsion, and vinyl acetate-acrylic emulsion.

4. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The phosphogypsum is obtained by drying, cooling and pulverizing waste phosphogypsum produced in industry; The particle size distribution of the phosphogypsum is below 0.3 mm.

5. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The cement can be replaced with a mixture of cement and mineral admixtures; The cement may be PO42.5 grade ordinary Portland cement, PO32.5 grade ordinary Portland cement, or sulfoaluminate cement.

6. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The specific gravity of the carbide slag is 2.7–2.9 g, and the particle diameter is 0.088–0.25 mm.

7. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The density of the silica fume is 2.20–2.50 g / cm³. 3 The average particle size is 0.1–0.3 μm, and the specific surface area is 22–26 m². 2 / g.

8. The semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 1, characterized in that, The density of the metakaolin is 2.50-2.60 g / cm³. 3 Specific surface area is 15-20m² 2 / g.

9. A method for preparing a semi-rigid, freeze-thaw resistant, and fatigue-resistant phosphogypsum pavement base material, characterized in that, The preparation of the semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material according to any one of claims 1 to 8 includes the following steps: Waste phosphogypsum is dried, cooled, crushed, and sieved to obtain the phosphogypsum. The phosphogypsum is mixed evenly with the cement, the carbide slag, the silica fume, and the metakaolin to obtain mixture A; After mixing the composite emulsion with water and stirring until homogeneous, mixture B is obtained; After mixing the mixture A and the mixture B evenly, the semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material is obtained.

10. The preparation method of the semi-rigid antifreeze and fatigue-resistant phosphogypsum pavement base material as described in claim 9, characterized in that, The temperature during the drying process of the waste phosphogypsum is controlled at 70℃~120℃, and the time is controlled at 12h~16h.